2007
DOI: 10.1016/j.aca.2007.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carbon nanotubes as a solid-phase extraction adsorbent for the extraction of cephalosporins antibiotics, sulfonamides and phenolic compounds from aqueous solution

Abstract: The adsorptive potential of carbon nanotubes (single-walled carbon nanotubes and multi-walled carbon nanotubes) for solid-phase extraction of three groups of highly polar compounds (namely cephalosporins antibiotics, sulfonamides and phenolic compounds) was tested in this article. The analytes were strongly retained by the carbon nanotubes. And acceptable recoveries were obtained with the addition of ammonium acetate into eluents. The effects of solution pH on the recoveries of the antibiotics and phenolic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…The difference of SPY degradation rates was likely related to the SPY speciation under different pH values. SPY has pK a1 and pK a2 values of 2.74 and 8.29 (Niu et al, 2007). Under acidic and alkaline environment different SPY speciation might affect the absorption of light wavelength (Fig.…”
Section: Spy Photodegradation At Varying Phmentioning
confidence: 99%
“…The difference of SPY degradation rates was likely related to the SPY speciation under different pH values. SPY has pK a1 and pK a2 values of 2.74 and 8.29 (Niu et al, 2007). Under acidic and alkaline environment different SPY speciation might affect the absorption of light wavelength (Fig.…”
Section: Spy Photodegradation At Varying Phmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have attracted much interest that was directed toward exploiting their unique thermal, mechanical, electronic and chemical properties [25] since discovered. The multi-walled CNTs (MWCNTs) composed of several rolled-up graphite sheets [26] displayed large specific surface areas [27] and high adsorption capacity [28], which was primarily owe to their dramatically hydrophobic surface and unique structure with internal tube cavity [29].…”
Section: Introductionmentioning
confidence: 99%
“…Limit of quantification was 0.5 μg/ kg for three barbiturates. The adsorptive potential of SWCNTs and MWCNTs for SPE of three groups of highly polar compounds (namely cefalosporin antibiotics, sulfonamides and phenolic compounds) was tested (Niu et al, 2007). It was found that the analytes were strongly retained by carbon nanotubes.Acceptable recoveries were obtained by adding ammonium acetate into the eluents.…”
Section: Carbon Nanotubes As a New Solid Phase Extraction Sorbent Formentioning
confidence: 99%